Frailty, depression, and quality of life in acute care for elderly: a serial mediation and moderated mediation study in Taiwan - Chau-Nee Chen; Tzu-Jung Fang; Cheng-Fang Hsieh; Chun-Chang Chen; Yu-Fu Chen; Hong-Yaw Chen; Pin-Yu Lai; Yu-Han Lu; Hon-Yi Shi (International Journal for Quality in Health Care, 2026)
Abstract Background Although the acute care for the elderly (ACE) model has been studied in relation to activities of daily living (ADL), depressive symptoms, and quality of life, the pathways linking frailty with post-discharge quality of life remain insufficiently understood. This study examined whether ADL and depressive symptoms sequentially mediated the association between frailty and quality of life among elderly patients receiving acute care. Methods This retrospective cohort study with longitudinal follow-up included 11,231 elderly acute care patients from three large medical centers in Taiwan between January 1, 2020, and June 30, 2023. Frailty, ADL, depressive symptoms, and quality of life were assessed at admission and one year after discharge using the Clinical Frailty Scale, ADL scale, Geriatric Depression Scale, and EQ-5D-3L. Serial mediation and moderated mediation analyses were conducted using the PROCESS macro in SPSS version 23.0. Results One-year ADL and depressive symptoms sequentially mediated the association between admission frailty and one-year quality of life (indirect effect = 0.131, 95% CI 0.038∼0.231). Frailty scores significantly decreased and ADL scores improved from admission to one year after discharge (p < 0.05). Moderated mediation analyses showed that BMI, Charlson Comorbidity Index, alcohol use, nasogastric tube placement, and nutritional status modified specific mediation pathways (p < 0.001). Conclusion Frailty among elderly patients receiving acute care was associated with post-discharge quality of life through pathways involving ADL and depressive symptoms. It supports comprehensive assessment and early post-discharge interventions targeting functional and psychological well-being, while recognizing that causal relationships cannot be established from observational data.